Identification of genetic loci for flag-leaf-related traits in wheat (Triticum aestivum L.) and their effects on grain yield - Wang, Ying; Qiao, Ling; Yang, Chenkang; Li, Xiaohua; Zhao, Jiajia; Wu, Bangbang; Zheng, Xingwei; Li, Pengbo; Zheng, Jun (Frontiers in Plant Science, 2022)
Flag-leaf-related traits including length (FLL), width (FLW), area (FLA), thickness (FLT), and volume (FLV) of flag leaves are the most important determinants of plant architecture and yield in wheat. Understanding the genetic basis of these traits could accelerate the breeding of high yield wheat varieties. The present study used a doubled haploid (DH) population to identify quantitative trait loci (QTL) for five flag-leaf-related traits and to analyze their correlation with grain-yield-related traits. Leaf thickness at two-thirds of the leaf length from tip to collar represented the average leaf thickness as measured with freehand sections and was used to calculate the leaf volume. This approach is a new means to easily measure FLV. A total of 79 QTL controlling the five traits were detected, explaining 3.09%-14.52% of the phenotypic variation. Among them, 15 stable QTL were identified, including two major QTL for FLT, six for FLW, three for FLA, two for FLT and two for FLV. QFLL-4A, QFLW-4B, QFLA-5D.1, QFLA-7A, QFLA-7D.1, QFLT-2B, QFLT-6A, QFLV-2A and QFLV-7D are likely novel loci. In addition, flag-leaf-related traits and grain-yield-related traits were significantly correlated. Taken together, these results provide a better understanding of the genetic basis underlying flag-leaf-related traits. Also, target regions for fine mapping and marker-assisted selection were identified and these will be valuable for breeding high yielding bread wheat.